Makna Gramatikal Punning Phrase Dajare dalam Kanal Youtube Shakishakinashi-Zu - Desy Irmayanti; Vira Yuniar Anggraini (IZUMI, 2023)
Dajare is a kind of Japanese wordplay in which a bad or unfunny joke is created by using the same or similar-sounding phrases or words. This uniqueness makes dajare interesting to analyze further in terms of its grammatical meaning of punning phrase dajare. The source of the data used in this study is a YouTube channel about Japanese prefectures. Dajare about prefectures would be very helpful in memorizing the names of Japanese prefectures. Based on that, this study aims to describe the meaning of punning phrase dajare on the Shakishakinashi-zu YouTube channel. Researchers use the theory of grammatical meaning by Sutedi. As a guideline, a qualitative descriptive method was used to analyze the data in this study. In this study, 42 of the 47 total data had grammatical meaning. The punny phrase dajare about Japanese prefectures was found to use the most grammatical meanings of the types of formation of language units found in 19 data, followed by 16 affixation data, 4 compounding data, and 2 reduplication data.    gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor